Spinal cord injury modeling: from modeling to evaluation using rats as examples - Wang, Shuai; Cai, Suying; Zhu, Zhemin; Zeng, Weibo; Hu, Shengxuan; Shi, Benchao (Frontiers in Neurology, 2025)
Spinal cord injury (SCI), with its enormous impact on individuals and society, seriously affects patients’ quality of life and is the focus and challenge of current medical research. The selection of appropriate SCI models and the reduction of heterogeneity between models are crucial for basic research on SCI. Although many articles have summarized and compared various SCI models, there are limited descriptions of how to further select the model animals after selecting the type of model, the degree of SCI, the use of anesthesia and analgesia, experience with modeling techniques, preoperative and postoperative care, management of common complications, sample collection, and evaluation of the spinal cord after injury. This paper aims to provide a practical guide for researchers who need to construct SCI models by combining the experimental experience of our research team in modeling and other related research literature. These guidelines will promote the standardization of SCI models, thus providing a solid foundation for in-depth research on SCI and the development of therapeutic strategies.